2018
DOI: 10.4317/medoral.21925
|View full text |Cite
|
Sign up to set email alerts
|

Is arthrocentesis of temporomandibular joint with corticosteroids beneficial? A systematic review

Abstract: BackgroundTemporomandibular disorders (TMDs) are musculoskeletal conditions that can inhibit the normal function of temporomandibular joints (TMJs) and affect the patient’s quality of life, negatively. Arthrocentesis (AC) is a minimally invasive surgical procedure used for treating TMDs. The aim of present paper is to evaluate the advantages of administrating corticosteroid (CS) during AC by reviewing high quality released articles.Material and MethodsSearching on Cochrane Library, Web of Science, Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(93 reference statements)
0
10
0
3
Order By: Relevance
“…The arthrocentesis technique was introduced at about 30 years ago [8] and it has been largely used along with other treatments, such as infiltrations of sodium hyaluronate [12], intra-articular analgesics [13], corticosteroids [14] and platelet rich plasm [15]. However, the literature has showed that an investigation regarding the isolated effects of the arthrocentesis over the DDWOR along with a clinical analysis performed with the aid of the Magnetic Resonance Imaging (MRI) may elucidate some of the benefits of this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The arthrocentesis technique was introduced at about 30 years ago [8] and it has been largely used along with other treatments, such as infiltrations of sodium hyaluronate [12], intra-articular analgesics [13], corticosteroids [14] and platelet rich plasm [15]. However, the literature has showed that an investigation regarding the isolated effects of the arthrocentesis over the DDWOR along with a clinical analysis performed with the aid of the Magnetic Resonance Imaging (MRI) may elucidate some of the benefits of this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[33] The most common complaint that causes the patient to refer to the physician in TMD is pain, and clinical outcome is the accompanying limitation in jaw movements. [2,14,27] These two factors negatively affect the daily lives of individuals. Reducing pain and limitation are of the most important goals in treatment of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Distance between superior and inferior incisive teeth's midpoint was taken as reference for this measurement. [2] MRI images were obtained with a 1.5 T MR imaging system (Philips Achieva; Philips Medical Systems, Best, the Netherlands) with a surface array coil. Proton density weighted (PDW) turbo spin echo sequences were taken in the sagittal plane in the closed-opened mouth position and in the coronal-sagittal plane in the closed mouth position.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have investigated the injection of corticosteroids with local anesthesia into the joint and reported good results in terms of pain management and improvement of function [53]. The corticosteroids commonly used intra-articular are betamethasone, methylprednisolone, dexamethasone and triamcinolone [54]. Corticosteroids suppress the inflammatory process inside the joint via prevention of the expression of cytokines and inflammatory mediators through binding to specific receptors [51].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%